Pengaruh Jenis Alat Pemanas Kandang Indukan terhadap Performan Layer Periode Starter - Dede Risnajati (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2011)
The study aimed to determine the influence of heater type on performance of laying hens during starter period and to identify the heater that produce the best performance in layer starter period. A total of 360 layer starter period is divided into two treatment groups of brooding cage with 2 of type heaters: heater ducting and heater portable. The data were then analyzed using t test. The results of the experiment indicated that the type of heater did not affect feed and consumption, body weight gain, feed conversion and uniformity of body weight of the layer starter period.